1992
DOI: 10.1007/bf01135566
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative EEG in elderly depressives

Abstract: Thirty-one elderly depressive patients were evaluated with topographic, quantitative EEG using relative measures, absolute measures, and computations of interhemispheric asymmetry and interhemispheric coherence in four frequency bands: delta, theta, alpha and beta. Patients were found to have lower than normal delta, higher than normal theta, higher than normal alpha and lower than normal beta values. EEG values were greater over the left than the right hemisphere in theta, alpha and beta bands. Lower than nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 15 publications
6
25
0
2
Order By: Relevance
“…In MDD a consistent finding is an elevated absolute [66,67,68,69,70] or relative alpha power [71,72] at mainly parietal and frontal [68,73] or occipital sites [74]. The reason that some studies did not find alpha power differences between patients and HCs [75,76] or found decreased (relative) alpha activity in comparison to other patient groups [77] might be related to differences of recording periods, where shorter recording periods prevent the differences described above [38,39] in vigilance regulation to occur (e.g.…”
Section: Biomarkersmentioning
confidence: 63%
See 1 more Smart Citation
“…In MDD a consistent finding is an elevated absolute [66,67,68,69,70] or relative alpha power [71,72] at mainly parietal and frontal [68,73] or occipital sites [74]. The reason that some studies did not find alpha power differences between patients and HCs [75,76] or found decreased (relative) alpha activity in comparison to other patient groups [77] might be related to differences of recording periods, where shorter recording periods prevent the differences described above [38,39] in vigilance regulation to occur (e.g.…”
Section: Biomarkersmentioning
confidence: 63%
“…Several studies have reported elevated slow-wave activity in MDD [69,98,99,100,101], with the focus of this elevated theta activity localized to frontal areas and often to the anterior cingulate cortex (ACC) [68,101,102], though decreased ACC activity in MDD has also been reported [103] and some studies found no differences between MDD and controls [104,105]. …”
Section: Biomarkersmentioning
confidence: 99%
“…The inverse relation between alpha power in EEG and cortical activation (Cook, O'Hara, Uijtdehaage, Mandelkern, & Leuchter, 1998) can reflect cortical hypoactivation in these areas of the brain. Several studies reported an increase in slow-wave activity over the right (Kwon, Youn, & Jung, 1996;Volf & Passynkova, 2002) and left (Roemer, Shagass, Dubin, Jaffe, & Siegal, 1992) hemispheres.…”
Section: Introductionmentioning
confidence: 99%
“…Aplicase o EEGq no diagnóstico e avaliação evolutiva das fases inicial ou intermediária das demências, quando os dados clínicos não tenham sido conclusivos (classe de evidência I I ) 5 4 . O aumento relativo da atividade lenta sugere org anicidade, ao contrário de depressão e ansiedade (classe de evidência III) [59][60][61][62][63][64][65][66][67][68][69] .…”
Section: Eletrencefalografia E Potenciais Evocadosunclassified